Electrochemical comparison of LiFePO4 synthesized by a solid-state method using either microwave heating or a tube furnace - Calderón, Cecilia Andrea (2017)
LiFePO4/C composites were successfully prepared by a solid-state reaction in order to compare conventional heat treatment and microwave-assisted synthesis at different times of sintering. Microwave-assisted synthesis is interesting due to the fact that energy and inert gas consumption can be greatly reduced with respect to the conventional treatment, resulting in a cheaper synthesis method. The relationship between particle morphology and crystal structure using the composite synthesis was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD) with refinements of the crystal structures carried out by the Rietveld method. In addition, the electrochemical performances were evaluated using constant current charge/discharge tests, cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS). It was observed that the samples prepared by microwave heating had a better electrochemical behavior than those prepared in a conventional furnace. Also, in general, a higher sintering time improved the electrochemical behavior, but with increased particle sizes, and consequently, a decreased specific capacity.